Gamifying programming education in K‐12: A review of programming curricula in seven countries and programming games. (11th September 2018) - Lindberg, Renny S. N.; Laine, Teemu H.; Haaranen, Lassi
Abstract: An increasing number of countries have recently included programming education in their curricula. Similarly, utilizing programming concepts in gameplay has become popular in the videogame industry. Although many games have been developed for learning to program, their variety and their correspondence to national curricula remain an uncharted territory. Consequently, this paper has three objectives. Firstly, an investigation on the guidelines on programming education in K‐12 in seven countries was performed by collecting curricula and other relevant data official from governmental and non‐profit educational websites. Secondly, a review of existing acquirable games that utilize programming topics in their gameplay was conducted by searching popular game stores. Lastly, we compared the curricula and made suggestions as to which age group the identified games would be suitable. The results of this study can be useful to educators and curriculum designers who wish to gamify programming education.